Upaya Membangun Karakter Siswa melalui Sinergitas Peran Guru dan Orangtua - Ruqoiyah, Ruqoiyah (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
The Indonesian nation is facing a dangerous situation at the moment due to character building whose effectiveness is not yet maximal and applicable. Information technology may develop rapidly, but the identity that is explored from the history of the origins of the nation which includes super culture must be preserved. This paper is intended to inspire enthusiasm, preserve character development with educational applicative tips through the synergy of the role of teachers and parents. With this synergy, the fulfillment of balanced needs is expected to optimize student growth and development in line with the nature of events that have been pinned to him as a human being. This is necessary because teachers and parents have a common mission of providing students with a thorough education both physically and spiritually. Thus teachers and parents have good opportunities to work together, work together to optimize the potential of students.